Effect of Lyophilized Lactoferrin on Cell Culture Arn8 in Normal Conditions and after Ultraviolet Irradiation - Galchenko, K. S. (Problems of Cryobiology and Cryomedicine, 2002)
The effect of lactoferrin (LF) on Arn8 cell culture in normal conditions and after ultraviolet (UV) irradiation has been studied. It was defined that LF did not initiate the progression of cells with damaged DNA into proliferation cycle. The effect of LF from bovine colostrum as well as human LF on Arn8 cells has been also studied. It was shown that incubation of cells with LF from bovine colostrum leads to much greater loss of cell viability than in cells incubated with human LF.